The battle of Varna in the Hungarian and Bulgarian tradition - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 1997)
The article concerns the functioning of the memory of the Battle of Varna in Hungarian and Balkan tradition. The author analyzes the way in which this event was preserved in chronicles, oral tradition, and the historical consciousness of the peoples of the region. The aim of the study is to compare the Hungarian and Balkan reception of the defeat at Varna and to indicate the factors influencing its limited resonance. The author employs an analysis of chronicles, epic traditions, and later historiography. The article demonstrates that in Hungary the memory of Varna was relatively weak, since John Hunyadi and his circle were not interested in promoting the memory of a defeat in which they played an ambiguous role. In Balkan tradition, the image of the battle was distorted by local epic accounts, and Varna itself was often not mentioned as the site of the clash. A stronger memory of the event was preserved only in Croatia. The author emphasizes that interest in the Battle of Varna developed only under the influence of nineteenth-century national movements and historical research of that period. The results of the analysis indicate that the significance of Varna in the historical tradition of the region was much smaller than modern European historiography suggests.